2021
DOI: 10.3748/wjg.v27.i29.4929
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune enteropathy and primary biliary cholangitis after proctocolectomy for ulcerative colitis: A case report and review of the literature

Abstract: BACKGROUND Autoimmune enteropathy (AIE) and primary biliary cholangitis (PBC) are both immune-mediated diseases. AIE or PBC complicated with ulcerative colitis (UC) are rare. There are no cases of AIE and PBC diagnosed after proctocolectomy for UC reported before, and the pathogenesis of these comorbidities has not been revealed. CASE SUMMARY A middle-aged woman diagnosed with UC underwent subtotal colectomy and ileostomy due to the steroid-resistant refractory disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…6 And PDC-E2 would trigger the formation of AMA-M2 in early-stage PBC, which was treated as a favourable diagnostic marker with high specificity and sensitivity from the results of a meta-analysis. 11,42 In our MR study, IVW as the main method indicated a significant and consistent causal relationship between IBD (UC and CD) and PBC. However, none of the results using the MR-Egger approach was significant which may result from the low statistical power of MR-Egger or the underestimation of causal effect due to the inflated type I error when all genetic variants are valid.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…6 And PDC-E2 would trigger the formation of AMA-M2 in early-stage PBC, which was treated as a favourable diagnostic marker with high specificity and sensitivity from the results of a meta-analysis. 11,42 In our MR study, IVW as the main method indicated a significant and consistent causal relationship between IBD (UC and CD) and PBC. However, none of the results using the MR-Egger approach was significant which may result from the low statistical power of MR-Egger or the underestimation of causal effect due to the inflated type I error when all genetic variants are valid.…”
Section: Discussionmentioning
confidence: 49%
“…The reactions between antibodies and homologues contribute to the break of self‐tolerance and immunological homeostasis within the liver 6 . And PDC‐E2 would trigger the formation of AMA‐M2 in early‐stage PBC, which was treated as a favourable diagnostic marker with high specificity and sensitivity from the results of a meta‐analysis 11,42 …”
Section: Discussionmentioning
confidence: 99%